Lynas Advance Material Plant (LAMP) Project: Examining factors influencing risk acceptance by the host community - Tengku Ismail , Tengku Hanidza; Hassan, Azman; Juahir, Hafizan; Md Zain, Sharifuddin; Abu Samah, Mohd Armi (Elsevier, 2015)
This paper provides an analysis of the local community response to the Lynas Advance Material Plant (LAMP) Project and the factors underlying their acceptance. A survey using a structured questionnaire, was conducted in 2013 (N=730). The predictors of risk acceptance by the host community: Fear + Trust, Benefits, and Confidence + Familiar (R2= 0.429). For the university community: Benefits, Fear + Safety, Knowledge, Familiar, and Confidence (R2= 0.623). The issue of lack of government understanding on public attitude, public concerns about the risk, and low confidence in government among the people living in proximity needs to be addressed.